The effect of human agility, digital literature, curriculum and the role of the family on the interest of the millennial generation in entrepreneurship through capabilities as intervening variables - Suherman, Asep; Yusuf (Journal of Economics and Business Letters, 2021)
The business environment continues to change rapidly and uncertainly, therefore, in order to exist, in the world of entrepreneurship, the millennial generation needs to have the capability to be able to exploit change and agility in action, or what is known as agility. Furthermore, with the support of knowledge of the rapidly growing digital world, nowadays, it is a determining factor for success in entrepreneurship. In particular, the issue of education and the role of the family that encourages the emergence of an entrepreneurial spirit in the millennial generation are also important factors that deserve to be reviewed. The data used by researchers in this study is primary data obtained through distributing questionnaires to active students at Pamulang University. Data collection was carried out in March 2021 and the analysis used using Structural Equation Model (SEM) analysis with the SmartPLS 3.0 software tool. Based on the results of the study, the human agility variable has a significant effect on entrepreneurial capabilities and interests, digital literacy variables only have a significant effect on capabilities, curriculum variables do not affect entrepreneurial capabilities or interests, family role variables only have a significant effect on capabilities, and capability variables affect entrepreneurial interests. However, the intervening variable capability is a good variable to influence the millennial generation's interest in entrepreneurship.